2023
DOI: 10.3390/f14101963
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Integration of Chemical Traits in Desert Plant Leaves with Variations in Soil Water and Salinity Habitats

Jifen Yang,
Xueni Zhang,
Danhong Song
et al.

Abstract: Understanding the relationship between soil environmental conditions and the interspecific integration of plant traits might shed light on how plants adapt to their environment. In order to clarify the adaptation strategies of desert plants in the various habitats, this study calculated interspecific trait integration (ITI) and plant trait networks (PTN) by selecting plants from high water-salinity habitat (HSM) with salt stress and low water-salinity habitat (LSM) with drought stress in the Ebinur Lake region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…The characteristics of plant trait networks can reflect the interaction between plants and the environment from a holistic perspective. The nodes represent the plant traits, and the lines between the nodes represent the correlations between the plant traits [37]. The correlations between the plant traits indicate the interactions between the traits [38].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of plant trait networks can reflect the interaction between plants and the environment from a holistic perspective. The nodes represent the plant traits, and the lines between the nodes represent the correlations between the plant traits [37]. The correlations between the plant traits indicate the interactions between the traits [38].…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…A correlation coefficient greater than 0.7 and p < 0.05 was considered to be a significant correlation between traits. The trait with the highest degree represented the "central trait" in the network [37]. Finally, Cytoscape software (Cytoscape 3.9.1) was used to visualize the network of plant functional traits.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…The adaptability of plants to a drought environment is realized through a series of complex physiological and biochemical mechanisms, including not only the absorption and efficient use of water but also the adjustment of their internal physiological and biochemical traits under drought stress. In order to clarify the adaptation strategies of desert plants in different habitats, Yang et al [6] focused on the interspecific integration of chemical traits in desert plant leaves with variations in soil water and salt habitats and found that the interspecific integration of plant leaf chemical traits in high water-salinity habitats was higher than that in low water-salinity habitats. Trait networks showed that C and Ca were the core leaf chemical traits for desert plant growth.…”
mentioning
confidence: 99%